PLANNING OF A DRY BULK WHARF IN CITAYUR, CILEGON, BANTEN - Lestari Budiarti, Tuti
Indonesia as a developing country, has been and will continue to have an increasingly significant infrastructure development. Various transportation infrastructure was built to fulfill the needs of the movement of people and goods distribution in Indonesia. As a maritime country with 2/3 of the whole territory is water, infrastructure development such as marine transportation infrastructure is necessary to be considered because transport through sea such as ships have advantages capable of transporting people and distribute goods in large enough quantities at a price which would cheaper than by land or air. As a prospective graduate civil engineering that will enter into work field, in this case work field that is still associated with the civil engineering, the author wanted this final project with respect of the planning and redesign the infrastructure wharf as one infrastructure marine transportation that can maximize the potential of maritime Indonesia , The planned wharf is located in Citayur, Banten and the dry bulk wharf is serving on unloading bulk cement as well planned as an open structure (Deck on Piles). Type pier built is marginal wharf structure type. In this thesis, the re-planning was done by design plate-type half slab and precast reinforced concrete beams, the calculation of the carrying capacity of piles of steel pipe pile, and the level of performance will be evaluated using a nonlinear static structure pushover analysis.